Principles of reinforced concrete design - Sozen, Mete Avni 1930-; Ichinose, Toshikatsu; Pujol, Santiago (Taylor & Francis, 2014)
The book covers fundamental concepts related to mechanics and direct observation, and those required to design reinforced concrete (RC) structures. Codes change constantly over time depending on factors that have little to do with the fundamental concepts mentioned, and have more to do with the markets, construction practices, and transient academic views. For beginning engineers it is difficult to distinguish between rules based on consensus (codes) and fundamentals. This book focuses on the latter to prepare the engineer to use and adapt to the constant changes of the former